Systematic theology; v. 2 - Tillich, Paul, 1886-1965 (Herts, U.K. Nisbet, 1957)
Contents : Part 3 : Existence and the Christ. Includes bibliographical references and index.
Donated by the Adelaide Assemblies, May, 1964
Keywords: Theology, doctrinal